Effect of different ways of application of Quitomax® in the growth of corn - Blanco-Valdes, Yaisys; Cartaya-Rubio, Omar Enrique; Espina-Nápoles, Meylen (Agronomía Mesoamericana, 2022)
Introduction. Corn (Zea mays L.) is a highly-consumed cereal in the world, which requires adequate fertilization to cover its nutritional requirements. Quitomax® is a biostimulant that has been successfully used to stimulate the yield of different crops. Objective. To evaluate the effectiveness of the application of Quitomax® on the growth of the improved Francisco variety corn crop. Materials and methods. The study was carried out in experimental areas of the National Institute of Agricultural Sciences (INCA) during 2018 and 2019, on a typical Ferralitic Red Leached eutric soil, with a randomized block experimental design with seven treatments and four replications. The Quitomax® treatments applied were: imbibition of the seeds for one hour at the concentrations of 0, 5 and 1 g L-1, foliar spray at the concentrations of 0, 5 and 1 g L-1, combination of both forms of application and concentrations, and a control. Yield and some of its components were evaluated. Results. The best results were obtained in the treatment that combined seed imbibition and foliar spraying (1 g L-1) (T6) of Quitomax®, with a yield of 12 t ha-1, plant height (A.P) of 2.12 m, mean diameter of the ear (DMM), and diameter of the stem (D. T) of 50.74 mm and 30.62 mm, respectively, height of the upper ear (AMS) of 1.13 cm, number of grains per row (NGH) and per ear (NGM) of 32.27 and 455.33, respectively, 17.53 cm ear length (LM), one hundred grain mass (M100S) of 38.90 g and 175.46 g total grain mass (MTSM). This treatment improved the benefit/cost ratio, and showed higher profits, although it was the most expensive. Conclusions. Seed and foliar application of Quitomax® was effective in increasing the yield and its components in corn.